Global Adipose Tissue Remodeling During the First Month of Postnatal Life in Mice - Bruder, Johanna; Fromme, Tobias (Frontiers in Endocrinology, 2022)
During the first month of postnatal life, adipose tissue depots of mice go through a drastic, but transient, remodeling process. Between postnatal days 10 and 20, several white fat depots display a strong and sudden surge in beige adipocyte emergence that reverts until day 30. At the same time, brown fat depots appear to undergo an opposite phenomenon. We comprehensively describe these events, their depot specificity and known environmental and genetic interactions, such as maternal diet, housing temperature and mouse strain. We further discuss potential mechanisms and plausible purposes, including the tempting hypothesis that postnatal transient remodeling creates a lasting adaptive capacity still detectable in adult animals. Finally, we propose postnatal adipose tissue remodeling as a model process to investigate mechanisms of beige adipocyte recruitment advantageous to cold exposure or adrenergic stimulation in its entirely endogenous sequence of events without external manipulation.